1995
DOI: 10.1016/0014-5793(95)00963-a
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of cAMP accumulation by the cloned Xenopus melatonin receptor through Gi and Gz proteins

Abstract: The Xenopus melatonin receptor was expressed in human embryonic kidney 293 cells and assayed for cAMP accumulation. In transfected 293 cells expressing the melatonin receptor, melatonin dose-dependently inhibited the endogenous adenylyi cyclases. In contrast, melatonin stimulated the accumulation of cAMP in cells co-expressing the type II adenylyl cyclase. Both the inhibitory and stimulatory responses to melatonin were mediated via Gi-like proteins as they were blocked by pertussis toxin. Upon co-transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 25 publications
(41 reference statements)
4
50
0
Order By: Relevance
“…These receptors are encoded by separate genes (Reppert et al 1994(Reppert et al , 1995(Reppert et al , 1996. Both melatonin receptors inhibit adenylyl cyclase via pertussis toxin-sensitive Gi proteins (Yung et al 1995;Barret et al 1999). The MT 1 receptor is localized in the hypothalamic SCN and hypophyseal pars tuberalis (Sugden et al 1999; revised by Dubocovich et al 2003).…”
mentioning
confidence: 99%
“…These receptors are encoded by separate genes (Reppert et al 1994(Reppert et al , 1995(Reppert et al , 1996. Both melatonin receptors inhibit adenylyl cyclase via pertussis toxin-sensitive Gi proteins (Yung et al 1995;Barret et al 1999). The MT 1 receptor is localized in the hypothalamic SCN and hypophyseal pars tuberalis (Sugden et al 1999; revised by Dubocovich et al 2003).…”
mentioning
confidence: 99%
“…Among the other known GPCRs expressed in the SCN, the receptors for serotonin (5-HT1A) and melatonin (MT1 and MT2) are also able to couple to Gz [33][34][35][36], extending a potential contribution of Gz to the circadian clock regulatory mechanisms.…”
Section: Gpr176 Couples To Gzmentioning
confidence: 99%
“…These results suggested that melatonin has enhanced the regulatory role of Ca 2+ /calmodulin pathway in sperm motility and velocity parameters including VCL and ALH in liquid storage of mithun semen. Moreover, melatonin has improved the mobility and velocity through act on the cyclic AMP (cAMP) stimulator (Yung et al, 1995) and cAMP stimulates sperm motility via its direct action on the axoneme of the tail (Lindamann, 1978) or indirectly through acting on the cell membrane as secondary messenger (Garbers and Kopf, 1980). Thus the melatonin treated sperm has higher motility and velocity parameters in the present study.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…It has been reported that melatonin has potency twice against peroxyl radicals as that of vitamin E in action (Pieri et al, 1994) and also it is more effective in scavenging of the hydroxyl radicals than mannitol and reduced glutathione (Hardeland et al, 1993). Melatonin is associated with mitochondrial membrane potential (Acuna-Castroviejo et al, 2011), ATP production (Chen et al, 1994), interaction with calmodulin (Tash et al, 1983), stimulates cellular influx of Ca2+ into sperm cells (Delgadillo et al, 1994) and cyclic AMP (cAMP) stimulator (Yung et al, 1995), through which the melatonin stimulate the sperm to get higher motility and velocity.…”
Section: Introductionmentioning
confidence: 99%